Asesmen Ranah Keterampilan dalam Pendidikan Agama Islam: Prinsip dan Pengembangan Instrumen - Retno Try Purnawati Retno; Jamil Suprihatiningrum; Eko Suwanto; Dani Alamsyah; Siti Sahra (LPPM Institut Pendidikan Nusantara Global, 2026)
This study examines the conceptual foundations and implementation of psychomotor assessment instruments in Islamic Religious Education (PAI) through a qualitative library research approach. Although skill-based assessment is an essential component of holistic learning evaluation, assessment practices in PAI classrooms remain predominantly focused on cognitive and affective domains, while psychomotor assessment is often implemented inconsistently and without contextually appropriate instruments. This study draws on books, journal articles, and other academic sources to analyse the principles, characteristics, and forms of skill assessment in PAI learning. The findings indicate that psychomotor assessment in PAI should not only evaluate technical performance, but also reflect the integration of cognitive understanding, affective commitment, and authentic religious practice. Effective assessment practices require the use of clear performance indicators, analytic rubrics, observation sheets, portfolios, authentic tasks, and self- or peer-assessment aligned with psychomotor taxonomies and authentic assessment principles. The study also identifies several challenges in implementing psychomotor assessment, including limited teacher assessment literacy, inadequate documentation systems, and the dominance of product-oriented evaluation practices. This study contributes to the discourse on Islamic education assessment by providing a conceptual understanding of skill-based assessment and offering practical considerations for developing more systematic and authentic psychomotor evaluation practices in PAI learning.